Antimicrobial resistance, prevalence of resistance genes, and molecular characterization in intestinal Bacteroides fragilis group isolates. Issue 6 (19th March 2019) - Kouhsari, Ebrahim; Mohammadzadeh, Nima; Kashanizadeh, Mohammad Ghasem; Saghafi, Mohammad Mehdi; Hallajzadeh, Masoumeh; Fattahi, Azam; Ahmadi, Alireza; Niknejad, Farhad; Ghafouri, Zahra; Asadi, Arezoo; Boujary Nasrabadi, Mohammad Reza
Abstract : Since the level of antimicrobial resistance in Bacteroides fragilis has increased, monitoring the antimicrobial susceptibility could be necessary. The objectives of this study were to (i) investigate the prevalence of species, the occurrence of reduced antimicrobial susceptibility (E‐test method), and antibiotic resistance genes in the B. fragilis group and (ii) evaluate the prevalence of enterotoxigenic B. fragilis and the distribution of bft gene subtypes in hospitalized patients. As many as 475 isolates out of 250 stool samples were detected to be B . fragilis group by using conventional biochemical tests (API‐32A system) and multiplex‐PCR. In addition, 48.2%, 13.9%, 76.6%, and 1.2% of B. fragilis group isolates were resistant (according to EUCAST breakpoint) to piperacillin‐tazobactam, meropenem, clindamycin, and metronidazole, respectively. Six metronidazole‐resistant strains were isolated; B. fragilis (n: 3), B. thetaiotaomicron, B. vulgates, and B . ovatus . The presence of the cfiA, cepA, ermF, and nim genes was observed in 3.8%, 15.9%, 34.1%, and 0.7% of the B. fragilis isolates, respectively. One hundred thirty‐two B. fragilis isolates (27.8%)and 21 B fragilis isolates (15.9%) turned out to be bft gene positive by multiplex‐PCR; eleven isolates (52.4%) harbored bft‐1, eight isolates (38%) harbored bft‐2 isotypes, and two isolates (9.5%) harbored bft‐3 isotype (16.66%). These bacteria harbor antimicrobial resistance genes that could be transferred to other susceptible intestinal strains. Further investigations on lineage analysis are needed for a better understanding of these bacteria in Iran.